Molecular identification of three of the most important mealybug species (Hemiptera: Sternorrhyncha: Coccoidea: Pseudococcidae) on ornamental plants in Guilan province, Iran - Hosseini, Reza; Hajizadeh, Jalil (Zootaxa, 2011)
Mealybugs (Coccoidea: Pseudococcidae) are serious pests, particularly as invasive species on many agricultural products. Morphological identification of mealybugs is based on adult female characters that, in the absence of adult females or with damaged specimens, can be problematic, especially when identification is required urgently, such as that involving the exportation/importation market. In this study, species-specific primers were designed to identify three of the most abundant mealybug species found on ornamental plants in Guilan province, Iran: Planococcus citri (Risso), Pseudococcus viburni (Signoret) and Pseudococcus comstocki (Kuwana). By generating amplification products of different sizes, the three species-specific primers, along with universal COI primers, were successfully used in multiplex PCR tests to identify all three mealybug species in a single reaction. Analysis of a large array of specimens from different geographic locations on different host plants showed that this was a reliable and accurate method.